2022
DOI: 10.1093/scan/nsac026
|View full text |Cite
|
Sign up to set email alerts
|

Differences in functional brain organization during gesture recognition between autistic and neurotypical individuals

Abstract: Persons with and without autism process sensory information differently. Differences in sensory processing are directly relevant to social functioning and communicative abilities, which are known to be hampered in persons with autism. We collected functional magnetic resonance imaging (fMRI) data from 25 autistic individuals and 25 neurotypical individuals while they performed a silent gesture recognition task. We exploited brain network topology, a holistic quantification of how networks within the brain are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Previous studies of TD children have indicated that neural networks can be positively coupled (for integration or cooperative activity, measuring ‘global efficiency’) or negatively coupled (resulting in functional segregation, measuring ‘local efficiency’) ( Trujillo et al ., 2022 ; Maliske et al ., 2023 ). As is shown in Figure 2A , the connection across networks was weaker than the mean connectivity strength within both cognitive and AE networks, which would confer segregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of TD children have indicated that neural networks can be positively coupled (for integration or cooperative activity, measuring ‘global efficiency’) or negatively coupled (resulting in functional segregation, measuring ‘local efficiency’) ( Trujillo et al ., 2022 ; Maliske et al ., 2023 ). As is shown in Figure 2A , the connection across networks was weaker than the mean connectivity strength within both cognitive and AE networks, which would confer segregation.…”
Section: Discussionmentioning
confidence: 99%
“…higher local efficiency) rather than the more integrative network organization seen in neurotypicals (i.e. higher global efficiency) ( Wadhera and Kakkar, 2021 ; Trujillo et al ., 2022 ), further representing that empathy network with short functional reach might be a compensation mechanism for processing empathy information in ASC, thus showing that weaker integration between empathic sub-networks is associated with better empathic ability. These results shed new light on the complex interplay between cognitive and AE processing in autism.…”
Section: Discussionmentioning
confidence: 99%
“…And other key issues that need to be solved urgently in the field of elderly care and medical care [6]. Nursing bed control system and human-computer interactive elderly nursing bed gesture recognition system [7]. Foreign gesture recognition technology developed earlier [8].…”
Section: Related Workmentioning
confidence: 99%